2011
DOI: 10.1007/s11430-011-4268-0
|View full text |Cite
|
Sign up to set email alerts
|

Depositional environment of terrestrial petroleum source rocks and geochemical indicators in the Songliao Basin

Abstract: To determine geochemical indicators for depositional environment favored by terrestrial petroleum source rocks, we selected 40 source rock samples from the Late Cretaceous Qingshankou Formation (K 2 qn) and the first member of Nenjiang Formation (K 2 n 1 ) in the Songliao Basin to qualify saturate fraction and aromatic fraction using GC-HRT (gas chromatography high resolution time-of-flight mass spectrometry) and quantify important biomarkers using GC-MS. The results reveal that source rocks from the 1st membe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(22 citation statements)
references
References 18 publications
0
19
0
3
Order By: Relevance
“…Contributing to the worldwide growth in production of unconventional oil and gas, tight oil has also been discovered in the sandstones of the second and third members of the Qingshankou Formation (K 2 qn 2+3 ) in the Songliao Basin (Shi et al, 2015). The Qingshankou Formation contains shale oil layers with high TOC and high oil yield near the base of its first (lower) member (K 2 qn 1 ; Feng et al, 2011). For this reason, over the past two decades, highresolution studies of the potential for hydrocarbon generation and the reconstruction of paleoenvironmental changes have been undertaken (Zhou and Littke, 1999;Jia et al, 2013b;Xu et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Contributing to the worldwide growth in production of unconventional oil and gas, tight oil has also been discovered in the sandstones of the second and third members of the Qingshankou Formation (K 2 qn 2+3 ) in the Songliao Basin (Shi et al, 2015). The Qingshankou Formation contains shale oil layers with high TOC and high oil yield near the base of its first (lower) member (K 2 qn 1 ; Feng et al, 2011). For this reason, over the past two decades, highresolution studies of the potential for hydrocarbon generation and the reconstruction of paleoenvironmental changes have been undertaken (Zhou and Littke, 1999;Jia et al, 2013b;Xu et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…The depositional environments and source of organic matter (OM) in Songliao source rocks has been extensively studied (Yang et al, 1981;Huang et al, 1998;Feng et al, 2009Feng et al, , 2011Chamberlain et al, 2013). Prior studies have shown that the Qiangshankou and Nenjiang Formations, the two major sets of OM-rich source rocks, were deposited in a deep freshwater lake, but under eutrophic and anoxic conditions Bechtel et al, 2012;Song et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Prior studies have shown that two large marine transgressions occurred during the Late Cretaceous, specifically during the Late Turonian (lower Qingshankou Formation) and the Late Santonianearly Campanian (lower Nenjiang Formation, K 2 n 1+2 ), depositing suites of dark mudstone, black shale, and oil shale (Yang et al, 1985;Feng et al, 2011). An increasing number of studies suggest that the formation of a hydrocarbon source rock in K 2 n 1+2 of the SLB relates to the marine transgression (Hou et al, 2000;Xi et al, 2011a;Huang et al, 2013;Hu et al, 2015).…”
Section: Mongolocypris Obscura Mongolocypris Tabulatamentioning
confidence: 99%